Effectiveness of Redecision Therapy on Rational Behavior and Psychological Well-being of Women - Tadayon Tajabadi, Fatemeh; Jafari, Forough; Fariborzi, Elham (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: The family is considered one of the important institutions. If it functions properly, family members will also enjoy health and well-being. The aim of the present study was to examine the effectiveness of redecision therapy on rational behavior and psychological well-being of married women aged 30 to 45 in Kerman city.Methods and Materials: The research method was quasi-experimental with a pre-test and post-test design with a control group. The statistical population included married women aged 30 to 45 who attended counseling centers in Kerman from October to November 2021. The sampling method was convenience sampling. The redecision therapy training sessions were conducted weekly for the experimental group over two and a half months, with each session lasting 90 minutes, based on the Goulding protocol (1979). The research instruments included the Psychological Well-being Questionnaire (Carl, 1989) and the Rational Behavior Questionnaire (Shorkey & Whiteman, 1997). Data analysis was performed in two sections: descriptive statistics and inferential statistics.Findings: The results showed that redecision therapy had a significant effect on increasing rational behavior (F=12.07, P